Analysis of the Effect of Profitability, Liquidity, and Firm Size on the Timeliness of Financial Report Submission - Ihsan Nasihin; Dian Purwandari (Jurnal Maksipreneur, 2022)
This research aims to analyze the factors that affect the timeliness of financial reports submitted to Indonesia Stock Exchange-listed manufacturing companies in the various industrial sectors. Profitability, liquidity, and firm size are the independent variable in this research, whereas the timeliness of financial report submission is the dependent variable. The population in this research were various industrial sector manufacturing companies listed on the IDX from 2012 to 2016. Sampling was carried out using the purposive sampling method to obtain 14 sample companies. The type of data used is secondary data obtained from the IDX website. The analytical method used is logistic regression analysis. Based on the results of logistic regression analysis with a significance level of 5%, the results of this research suggest that profitability (ROI) has no significant effect on the timeliness of financial report submission, while liquidity (CR), and company size (TA) have a significant effect on the timeliness of financial report submission.